Pengaruh Bukti Fisik terhadap Keputusan Berkunjung di Era New Normal di Kolam Renang Umbul Kating - Lucia Esti Setyaning; Victor Marindra Ardianto; Filiae Marry (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2022)
The purpose of this research is to analyze the effect of physical evidence on the decision to the visit new normalera at the swimming pool of Umbul Kating Desa Purwodadi Mekar. This research is a type of quantitative research. The sampling technique used is the accidental sampling technique, which is the technique of determining the sample based on chance, that is, anyone who coincidentally meets the researcher can be used as a sample, if it is deemed that the person who happened to be met is suitable as a data source, and in this study, 100 respondents were used. calculated by non-probability sampling using the Slovin formula. The technique used in this research was analyzed using simple linear regression analysis.The test results shown by the study obtained the equation regression Y = 9.809 + 0.296X + e. From the regression coefficient of the Physical Evidence (X) variable of 0.296. Based on R square() of 0.099, it shows that statistically the magnitude of the influence of Physical Evidence on Visiting Decisions in the Era New Normal at the swimming pool of Umbul Kating Desa Puwodadi Mekar is 9.9% while the other 90.1% is influenced by other factors that are not investigated in this study.